Ramen Restaurant Interior Design 1 With Communicative Restaurant Concept - Sumbawati, Suci; Atiqah, Annisaa Nurul; Deskarina, Rekta (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Culinary tourism is increasingly expanding in Yogyakarta. Japanese cuisine has become one of the popular commodities in Yogyakarta. Ramen 1 restaurant presents Japanese dishes with a concept of a traditional Japanese restaurant in its interior design. The aim of this study is to understand the meaning of the interior elements in Ramen 1. The research method used is a qualitative descriptive method. The results of this study indicate that the overall interior design of Ramen 1 restaurant has characteristics of simplicity, elegance, and harmony with nature, as seen in the selection of ornaments, color choices, and furniture. Wall ornaments that display menu descriptions not only function as ornaments but also serve as communicative information tools for visitors.